Therapeutic Effect, Chemical Composition, Ethnobotanical Profile of Eucalyptus globulus: A Review - Jafari, Fatemeh; Ramezani, Mahin; Nomani, Homa; Amiri, Mohammad S.; Moghadam, Ali Tafazoli; Sahebkar, Amirhossein; Emami, Seyed Ahmad; Mohammadpour, Amir Hooshang (Letters in Organic Chemistry, 2021)
The composition of essential oil (EO) of E. globulus is so different all over the world. The main component of essential oil is 1,8-cineole (Compound 64), macrocarpal C (Compound 22), terpenes (Compound 23-92), oleanolic acid (Compound 21), and tannins (Compound 93-99). We searched in vitro and in vivo articles and reviewed botanical aspects, therapeutic activity, chemical composition and mechanism of action of E. globulus. Essential oils and extracts of leaves, stump, wood, root and fruits of E. globulus represented many various medicinal effects including antibacterial, antifungal, antidiabetic, anticancer, anthelmintic, antiviral, antioxidant, anti-inflammatory, protection against UV-B, wound healing effect and stimulating the immune response. Also, the leaf extract of eucalyptus is used as a food additive in the industry. Eucalyptus has so many different therapeutic effects and some of these effects were confirmed by pharmacological and clinical studies. More clinical studies are recommended to confirm the useful pharmacological activity of E. globulus.
Keywords: in vitro studies